A dialética nos escritos do círculo de Bakhtin - Cardoso, Daniela (2013)
This study aims to accomplish a readback of Bakhtin Circle writings about language with dialectical assumptions presented by Marx and Engels in The Germany Ideology and Economic and Philosofical Manuscript. It seeks to recognize the dialectic-materialist character of the Bakhtin Circle conceptual proposals to define language. It is understood that in language, there is a mutual influence relation among otherness, dialogism and ideology, in the concrete enunciation and ultimately in the speech genre. The hypothesis that guides this study is that the elaborations of the Circle about the linguistic phenomenon are manifestations of a dialectical-materialist idea about the investigated reality/object.